Associations of circulating very-long-chain saturated fatty acids and incident type 2 diabetes: a pooled analysis of prospective cohort studies. Issue 4 (15th April 2019) - Fretts, Amanda M; Imamura, Fumiaki; Marklund, Matti; Micha, Renata; Wu, Jason H Y; Murphy, Rachel A; Chien, Kuo-Liong; McKnight, Barbara; Tintle, Nathan; Forouhi, Nita G; Qureshi, Waqas T; Virtanen, Jyrki K; et al.
ABSTRACT: Background: Saturated fatty acids (SFAs) of different chain lengths have unique metabolic and biological effects, and a small number of recent studies suggest that higher circulating concentrations of the very-long-chain SFAs (VLSFAs) arachidic acid (20:0), behenic acid (22:0), and lignoceric acid (24:0) are associated with a lower risk of diabetes. Confirmation of these findings in a large and diverse population is needed. Objective: We investigated the associations of circulating VLSFAs 20:0, 22:0, and 24:0 with incident type 2 diabetes in prospective studies. Methods: Twelve studies that are part of the Fatty Acids and Outcomes Research Consortium participated in the analysis. Using Cox or logistic regression within studies and an inverse-variance-weighted meta-analysis across studies, we examined the associations of VLSFAs 20:0, 22:0, and 24:0 with incident diabetes among 51, 431 participants. Results: There were 14, 276 cases of incident diabetes across participating studies. Higher circulating concentrations of 20:0, 22:0, and 24:0 were each associated with a lower risk of incident diabetes. Pooling across cohorts, the RR (95% CI) for incident diabetes comparing the 90th percentile to the 10th percentile was 0.78 (0.70, 0.87) for 20:0, 0.84 (0.77, 0.91) for 22:0, and 0.75 (0.69, 0.83) for 24:0 after adjustment for demographic, lifestyle, adiposity, and other health factors. Results were fully attenuated in exploratory models that adjusted for circulating 16:0 and triglycerides. Conclusions: Results from this pooled analysis indicate that higher concentrations of circulating VLSFAs 20:0, 22:0, and 24:0 are each associated with a lower risk of diabetes.